2008
DOI: 10.1371/journal.pone.0002379
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Phenotype Is Sustained by Selective MAPK Oxidation in Mitochondria

Abstract: Mitochondria are major cellular sources of hydrogen peroxide (H2O2), the production of which is modulated by oxygen availability and the mitochondrial energy state. An increase of steady-state cell H2O2 concentration is able to control the transition from proliferating to quiescent phenotypes and to signal the end of proliferation; in tumor cells thereby, low H2O2 due to defective mitochondrial metabolism can contribute to sustain proliferation. Mitogen-activated protein kinases (MAPKs) orchestrate signal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 52 publications
1
61
0
2
Order By: Relevance
“…AMs from acrolein-exposed mice were lysed and derivatized with BH for analysis of total carbonylated proteins by streptavidin blotting (B) or Western blot analysis of purified biotinylated proteins or input lysates for RelA or JNK (C). (67). By analogy, alkylation of these corresponding Cys residues within JNK or ERK might interfere with their interaction with upstream MEK proteins, and thereby contribute to the observed inhibition of their phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…AMs from acrolein-exposed mice were lysed and derivatized with BH for analysis of total carbonylated proteins by streptavidin blotting (B) or Western blot analysis of purified biotinylated proteins or input lysates for RelA or JNK (C). (67). By analogy, alkylation of these corresponding Cys residues within JNK or ERK might interfere with their interaction with upstream MEK proteins, and thereby contribute to the observed inhibition of their phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was shown that ERK1/2, as well as p38, JNK, and their respective MAPKKs, are present in the mitochondria of a murine tumor cell line, and the traffic of these MAPKs in and out of the organelle is regulated by hydrogen peroxide. 143 Another important step in understanding the mitochondrial localization, regulation, and role in mitochondrial activities was the recent proteomic study on ERK1/2-interacting proteins in the mitochondria. 96 In this study, it was demonstrated that ERK1 physically associates with structural, signaling, transport, and metabolic proteins in the mitochondria of HeLa cells.…”
Section: Erk1/2 In the Mitochondriamentioning
confidence: 99%
“…Additionally, evidence to support a role for direct redox regulation of several components of the MAPK signalling pathway (Greene et al,2000 ;Galli et al, 2008), re-inforces the early work of Adler et al (1999), who demonstrated the redox-dependent activation of JNK via the oxidative inactivation of its inhibitor GSH-S-transferase Pi.…”
Section: Rtks Such As the Insulin Receptor (Ir) Epidermal Growth Facmentioning
confidence: 85%
“…Recent evidence has identified a redox element in the direct regulation of c-Abl (Leonberg and Chai, 2007), Akt (Wani et al, 2011), c-AMP-dependent protein kinase (Humphries et al, 2005), Erk (Galli et al, 2008), Ca(2+)/calmodulindependent protein kinase (Erickson et al, 2008), cGMP-dependent protein kinase (PKG) Iα (Burgoyne et al, 2007), ataxia-telangiectasia mutated (ATM) protein kinase (Guo et al, 2010) and apoptosis signal-regulated kinase-1 (ASK-1) (Nadeau et al, 2007). Additionally, evidence to support a role for direct redox regulation of several components of the MAPK signalling pathway (Greene et al,2000 ;Galli et al, 2008), re-inforces the early work of Adler et al (1999), who demonstrated the redox-dependent activation of JNK via the oxidative inactivation of its inhibitor GSH-S-transferase Pi.…”
Section: Rtks Such As the Insulin Receptor (Ir) Epidermal Growth Facmentioning
confidence: 99%